2013
DOI: 10.1002/jgrd.50679
|View full text |Cite
|
Sign up to set email alerts
|

Idealized dry quasi 2‐D mesoscale simulations of cold‐air outbreaks over the marginal sea ice zone with fine and coarse resolution

Abstract: [1] A nonhydrostatic model (NH3D) is used for idealized dry quasi 2-D simulations of Arctic cold-air outbreaks using horizontal grid spacings between 1.25 and 60 km. Despite the idealized setup, the model results agree well with observations over Fram Strait. It is shown that an important characteristic of the flow regime during cold-air outbreaks is an ice-breeze jet (IBJ) with a maximum wind speed exceeding often the large-scale geostrophic wind speed. According to the present simulations, which agree very w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 145 publications
2
38
0
2
Order By: Relevance
“…We found the typical vertical temperature structure of a convective case with a well-mixed layer between the surface and a strong capping inversion together with an increasing temperature and atmospheric boundary layer height with distance from the ice edge. This documents the convective character of the ABL as found earlier during Fram Strait CAOs (Brümmer, 1997;Hartmann et al, 1997;Chechin et al, 2013;Lüpkes and Schlünzen, 1996;Wacker et al, 2005). The vertically averaged ABL potential temperature increased from 243 K at 64 km north of the ice edge by 18 K at 214 km south of it (Fig.…”
Section: Cold Air Outbreaks North Of Svalbard In March 2013supporting
confidence: 85%
See 1 more Smart Citation
“…We found the typical vertical temperature structure of a convective case with a well-mixed layer between the surface and a strong capping inversion together with an increasing temperature and atmospheric boundary layer height with distance from the ice edge. This documents the convective character of the ABL as found earlier during Fram Strait CAOs (Brümmer, 1997;Hartmann et al, 1997;Chechin et al, 2013;Lüpkes and Schlünzen, 1996;Wacker et al, 2005). The vertically averaged ABL potential temperature increased from 243 K at 64 km north of the ice edge by 18 K at 214 km south of it (Fig.…”
Section: Cold Air Outbreaks North Of Svalbard In March 2013supporting
confidence: 85%
“…The latter regions are of special interest for oceanatmosphere interactions due to frequent cold air outbreaks (CAOs) (e.g., Kolstad and Bracegirdle, 2008;Brümmer and Pohlmann, 2000;Chechin et al, 2013;Gryschka et al, 2008) with extremely large energy fluxes between ocean and atmosphere downstream of the ice margin. This means that, even if the number of CAOs remained unchanged, a position change of the ice edge would have a strong impact on the local temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lüpkes et al (2012b) determined that the simplest possibility for successfully parameterizing turbulent transport in a strong convective regime is to use closures allowing countergradient transport of heat. Applying a mesoscale model with different grid sizes, Chechin et al (2013) found for idealized cases that the strength of the ice breeze developing in CAOs over open water downstream of the MIZ was strongly affected by the grid sizes: models with grid sizes larger than 20 km tend to underestimate the wind speed close to the ice edge. This finding confirms earlier results by Renfrew et al (2009a, b) and Haine et al (2009).…”
Section: Atmosmentioning
confidence: 99%
“…There are also studies with mesoscale non-eddy resolving models (Wacker et al 2005;Chechin et al 2013) The (resolved) contributions by rolls (long dashed lines) and unorganized turbulence (short dashed lines) for the roll-case are shown, respectively. The solid black lines (appearing as almost one line, a, c) represent the subgrid-scale contributions to the total turbulent fluxes.…”
Section: Cold-air Outbreaksmentioning
confidence: 99%